The Response of Rice (Oryza sativa L.) to Organic Fertilizer Plus and Organic Pesticides under the System of Rice Intensification (SRI) in Tidal Lowlands - Neni Marlina; Eko Adi Saputro; Nurbaiti Amir (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Marlina et al. 2012. The Response of Rice (Oryza sativa L.) to Organic Fertilizer Plus and Organic Pesticides under the System of Rice Intensification (SRI) in Tidal Lowlands. JLSO 1(2):138-148. This study aims at evaluating the response of rice (Oryza sativa L.) to the dosage and type of organic fertilizer plus and organic pesticides under the System of Rice Intensification (SRI) in tidal lowlands. This research was implemented at the rice field Desa Tanjung Sari, Kecamatan Tanjung Lago, Kota Terpadu Mandiri  (KTM) Telang, Kabupaten Banyuasin. The research was conducted from December 2010 until March 2011. It employedFactorial Group Randomized Design (RAK) to allow each factor were repeated 3 times for 5 plant samples. Variability analysis indicates that the provision of the dosage of organic fertilizer plus provided significant  effect on plant height, the number of seedlings, the number of productive seedlings, grain per panicle, production, and the percentage of infestation. However, it did not show significant  effect on the percentage of empty grains. The provision of organic pesticides provided significant effect on grain per panicle, production, the percentage of pests, but gave no effect on plant height, the number of seedlings, the number of productive seedlings, and the percentage of empty grains. The combination of powdered organic fertilizer plus of  750 kg / ha and  organic pesticides (animal and vegetable pesticides) gave  the highest production of 2.23 kg/plot or 5.57 ton/ha.